République Démocratique du Congo: Impacts du COVID-19 sur la production, la pauvreté et le système alimentaire - Pauw, Karl; Randriamamonjy, Josee; Thurlow, James; Ulimwengu, John M. (2021)
Karl Pauw, Josée Randriamamonjy, James Thurlow, et John Ulimwengu IFPRI